Chagos in ‘Blue’: - Anonymous Author (Cidades, Comunidades e Território)
Around 1500 Chagos Islanders were expelled from the Chagos Archipelago and moved to Mauritius and Seychelles between 1965 and 1973. Diego Garcia, the largest island of the Chagos, became a US military base. The Chagos Marine Protected Area (MPA) was established in 2010 and currently acts as legal ammunition against Chagossians’ claims for their rights of return and abode. This article uncovers the multi-layered impacts of the Chagos MPA as fortress conservation by conducting a multiscale spatial analysis and addresses the epistemic system(s) of power. It pays particular attention to colonial and imperial legacies in the construction of environmental science, a planetary-scale archipelagic network, and the rhetoric of ecological (in)security. The politics of coconut manifested in the Barton Point restoration project substantiates claims of spatial and epistemic violence. This article further describes Chagossian strategies of resistance using the works of Clement Siatous and Shenaz Patel. It concludes by arguing against the coupling of military occupation with an environmental fortress that conceals and perpetuates historical injustice. Chagos ecology is storied, layered and laminated through human–land interactions. Chagossians’ imaginative accounts of a shared homeland are inspirational manifestos.